Etika Dakwah dan Regulasi Penyiaran Agama di Era Digital: Relevansi Normatif dan Tantangannya bagi Kerukunan Umat Beragama - Hendra, Tomi (Jurnal Komunikasi Islam, 2026)
The development of digital media has transformed the dissemination of religious messages from a centralized form of communication to a more open one. This shift has expanded opportunities for da’wah, but at the same time increases the risk of disrupting interfaith harmony. This study aims to analyze the relevance of religious broadcasting regulations and da’wah ethics in strengthening interfaith harmony in the digital age. The study employs a qualitative approach through a literature review, examining regulations, documents related to religious broadcasting, and academic literature on da’wah, religious communication, digital media, and interfaith harmony. The results of the analysis indicate that regulations on religious broadcasting remain normatively relevant in upholding respect for religious freedom and interfaith harmony, but they have technical limitations in addressing the participatory and algorithm-based nature of digital media. Therefore, formal regulations need to be strengthened through the application of da’wah ethics, digital literacy, and communicative responsibility so that the dissemination of religious messages can take place in a dialogical, inclusive manner oriented toward strengthening interfaith harmony.